2010
DOI: 10.1007/s00442-010-1847-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal nested patterns in macroinvertebrate assemblages across a pond network with a wide hydroperiod range

Abstract: Nestedness has been widely used to measure the structure of biological communities and occurs when species-poor sites contain subsets of species-rich ones. Here, we examine nested patterns across the macroinvertebrate assemblages of 91 ponds in Doñana National Park, Spain, and explore temporal variation of nestedness and species richness in 19 temporary ponds over 2 years with differing rainfall. Macroinvertebrate assemblages were significantly nested; both pond spatial arrangement and environmental variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 62 publications
2
41
0
1
Order By: Relevance
“…As observed by Ebert & Balko (1987) and Florencio et al (2011), isolation in time, as resulting from the different length of hydroperiod among the ponds of a network, can give similar patterns to those observed when it occurs in space, further confirming that both pond density and hydroperiod length in a given area are important in determining the colonization chances (Ruhí et al, 2013).…”
Section: Environmental Filterssupporting
confidence: 77%
See 1 more Smart Citation
“…As observed by Ebert & Balko (1987) and Florencio et al (2011), isolation in time, as resulting from the different length of hydroperiod among the ponds of a network, can give similar patterns to those observed when it occurs in space, further confirming that both pond density and hydroperiod length in a given area are important in determining the colonization chances (Ruhí et al, 2013).…”
Section: Environmental Filterssupporting
confidence: 77%
“…Conversely, in a study carried out in a network of temporary ponds, Eitam et al (2004) found that crustacean species richness was positively related to hydroperiod length but not to surface area. This result could be explained by the assumption that increased isolation of ponds due to the progressive disappearing of the aquatic habitat during the dry phase, as it may occur in a network of temporary ponds with different hydroperiods, can limit local immigration and unbalance the immigration/extinction patterns generating nested patterns of ponds with species-poor sites containing a subset of species-rich sites (Florencio et al, 2011). The degree of nestedness thus quantifies the overlap in species composition between high and low diversity areas (McAbendroth et al, 2005).…”
Section: Environmental Filtersmentioning
confidence: 99%
“…Doñana's temporary ponds have been revealed to be a robust and interconnected network when it comes to the dispersal of macroinvertebrates and their recolonisation of ponds (Florencio et al, 2011). Therefore, we consider it improbable that, in our study, dispersal limitations would be driving changes in microcrustacean assemblages.…”
Section: Discussionmentioning
confidence: 92%
“…It is considered a single aquifer from the perspective of groundwater dynamic although it has been recently divided in 5 sections from a water management point of view [7]. The Doñana's system of Mediterranean temporary ponds on the aeolian sands has received substantial attention from the perspective of its hydrology [8,9], geomorphology [10][11][12], relation to groundwater [4,13,14], water chemistry [15,16], biodiversity [17][18][19][20] but most studies have been conducted in a few ponds and only for a few years.…”
Section: Introductionmentioning
confidence: 99%